FORMING A READING CULTURE IN PRIMARY GRADES - Erdosheva Iroda Alisher qizi (Ethiopian International Journal of Multidisciplinary Research, 2026)
This article analyzes the pedagogical, psychological and methodological foundations of the formation of a reading culture in primary school students. Reading culture is highlighted as an important factor in developing the intellectual potential of students, forming independent thinking skills, and improving their spiritual and moral education. It also reveals the issues of effective use of fiction in the process of primary education, increasing students' interest in reading, and organizing reading activities based on modern pedagogical technologies.